Effect Of Different Carbon and Nitrogen Sources on the Activity of Cycloamylase (Cyclomaltodextrin Glucanotransferase) Produced By Sutclifella cohnii - Odunayo Selimot Adedeji; Zainab Abdulazeez; Oluwafemi Adebayo Oyewole; Adamu Yusuf Kabiru; Evans Chidi Egwim (Nepal Journal of Biotechnology)
Cyclomaltodextrin glucanotransferase (CGTase) is an important group of microbial amylolytic enzyme that helps in the conversion of starch and other polysaccharides into cyclic oligosaccharides. This study was carried out to determine the effect of alternative carbon and nitrogen sources on the production of cyclomaltodextrin glucanotransferase from Sutclifella cohni. Rice- soybean water (RS), yam-soybean water (YS), rice-fish water (RF), fufu-fish water (FuF), fufu- soybean water (FuS), rice-meat water (RM), yam-meat water (YM), fufu-meat water (FuM), and yam-fish water (YF) were used as substitute for soluble potato starch in the production medium.. The different carbon and nitrogen sources studied supported the growth and production of CGTase. The optimal pH and temperature was 8.0 and 45oC, respectively. The lowest Km (4.17 mg/mL) was observed with RM as the growth medium. This study concludes that food waste could be used as substitute for soluble starch in the production of CGTase, for industrial application.